Features of the microbiota in chronic apical periodontitis. A systematic review - Z. S. Khabadze; A. Wehbe; Y. A. Bakaev (Эндодонтия Today)
Introduction. The article describes the microbiota found in teeth with chronic apical periodontitis.Materials and methods. Electronic research of English and Russian literature was carried out in January 2022, in the databases of PubMed, Google scholar, Scopus, ResearchGate and ScienceDirect. The search started on the 10th of January 2022 and ended on the 12th of January 2022. A total of 23 articles were selected, 17 of which were selected for detailed review. Chief question in this article was: which microbial communities are present in root canals diagnosed with CAP? And how are they associated with clinical symptomatology?Results. The inhabitants of the root canals with chronic apical periodontitis are mainly facultative anaerobes.Conclusions. The microbiota of chronic apical periodontitis is very diverse, some of its main inhabitants are E. faecalis, P. acnes, F. nucleatum, streptococcus spp, and P. gingivalis. Some authors have found that E. faecalis corresponded to 17% and up to 99.8% of the total bacterial counts present in the root canal with CAP. the presence of P. gingivalis was associated with tenderness to percussion, the presence of E. faecalis, F. nucleatem, and P. gingivalis were associated with periapical lesions > 3 mm, and the presence of P. acnes, S. mitis and E. faecium showed persistent exudation.